PERAN MULTINATIONAL CORPORATION PT. TOYOTA MOTOR MANUFACTURING INDONESIA DALAM PENGEMBANGAN SUMBER DAYA MANUSIA UNTUK MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS - Muhammad Azzam Hikari (2024)
This research analyzes the role of Multinational Corporation (MNC) PT. Toyota Motor Manufacturing Indonesia (TMMIN) in developing human resources to achieve Sustainable Development Goals (SDGs) point 4. Through descriptive qualitative research methods, the research used documentation study techniques and interviews with the Section Head of the Toyota Indonesia Academy. The research results show that TMMIN has successfully implemented a number of CSR programs, such as Toyota Indonesia Academy (TIA), Development of Vocational Schools for Vocational High Schools, Toyota Eco Youth (TEY), Apprenticeship Program, Link and Match University, and Human Resource Development in Small and Medium Industries (SMIs), which are significant in supporting SDGs Point 4 related to Quality Education. In addition, by referring to Carroll's 1991 CSR Pyramid, this company has succeeded in demonstrating commitment to four levels of responsibility, namely Economic Responsibility, Legal Responsibility, Ethical Responsibility and Philanthropic Responsibility.